2007
DOI: 10.3748/wjg.13.6115
|View full text |Cite
|
Sign up to set email alerts
|

Epidermal growth factor receptor antibody plus recombinant human endostatin in treatment of hepatic metastases after remnant gastric cancer resection

Abstract: We report a 55-year-old male who developed advanced hepatic metastasis and peritoneal carcinomatosis after resection of remnant gastric cancer resection 3 mo ago. The patient only received epidermal growth factor (EGF) receptor antibody (Cetuximab) plus recombinant human endostatin (Endostar). Anti-tumor activity was assessed by 18 F-fluorodeoxyglucose ( 18 F-FDG) positron emission tomography/computer tomography (PET/CT) at baseline and then every 4 wk. The case illustrates that 18 FDG-PET/CT could make an ear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 6 publications
0
9
0
Order By: Relevance
“…Many studies reported that the expressions of EGF and VEGF were related to the invasion and metastasis of gastric cancer cells [5][6][7] . EGF belongs to polypeptide growth factors and widely exists in the tissues and body fluids in both human beings and animals.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies reported that the expressions of EGF and VEGF were related to the invasion and metastasis of gastric cancer cells [5][6][7] . EGF belongs to polypeptide growth factors and widely exists in the tissues and body fluids in both human beings and animals.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, endostatin has re-entered the clinic in a modified form that renders it more stable [38]. This modified version is now used in certain countries for the treatment of lung and gastric cancer [39, 40]. …”
Section: Endostatin—a Stroma Derived Tumor Biomarker?mentioning
confidence: 99%
“…This modification results in a more stable molecule with similar anti-angiogenic activity [70]. This modified endostatin is now used in certain countries for the treatment of lung and gastric cancer [72,73]. Interestingly, it has recently been shown that the levels of circulating endothelial cells and survivinin may be ideal markers predicting efficacy of endostatin treatment in patients with lung cancer [74].…”
Section: Type XVIII Collagen Derived Endostatinmentioning
confidence: 99%